2004
DOI: 10.1136/adc.2002.025924
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low birth weight and body size in early adulthood

Abstract: Aims: To determine the body size of extremely low birth weight (ELBW, birth weight 500-999 g) subjects in early adulthood. Methods: Cohort study examining the height and weight of 42 ELBW survivors free of cerebral palsy between birth and 20 years of age. Weight and height measurements were converted to Z (SD) scores. Results: At birth the subjects had weight Z scores substantially below zero (mean birth weight Z score 20.90, 95% CI 21.25 to 20.54), and had been lighter than average at ages 2, 5, and 8 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
69
2
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 11 publications
9
69
2
7
Order By: Relevance
“…Multiple logistic regression of the association between underweight at 5 years and physical characteristics at birth in low birth weight children. adults born preterm or LBW have also been shown to be shorter and lighter than their peers [9] [10] [28] [30] [31]. For example, Saigal et al [31] reported that the mean height of young adults born extremely LBW (<1.0 kg) was below their target height.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple logistic regression of the association between underweight at 5 years and physical characteristics at birth in low birth weight children. adults born preterm or LBW have also been shown to be shorter and lighter than their peers [9] [10] [28] [30] [31]. For example, Saigal et al [31] reported that the mean height of young adults born extremely LBW (<1.0 kg) was below their target height.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have reported retarded height and weight growth among LBW, especially in VLBW children [10] [11]. Although most LBW children experience catch-up growth by adolescence, the precise time of catch-up is highly diverse and appears to depend on their weight and gestational age at birth [6]- [9]. In fact, several studies have reported that SGA infants were more likely to remain smaller throughout childhood and adulthood than infants born at weights appropriate for gestational age (AGA) [8] [11] [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Around 10% will exhibit weight and height below the 3rd percentile, differences are not observed in terms of sexual maturity or body composition. 13,48,49 The fact that ELW children progress with smaller stature until adolescence leads to questions about the possibility of growth hormone use, but in few studies has bone age been tested and when hormone has been used results have been inconclusive. 13,40 There is not currently enough evidence to recommend this treatment.…”
Section: Growth Prognosis For Elw Preterms Up To Adolescence and Adulmentioning
confidence: 99%
“…One important result that merits further investigation was the occurrence of overweight among 1/3 of the cohort with obesity at 10%. 49 …”
Section: Growth Prognosis For Elw Preterms Up To Adolescence and Adulmentioning
confidence: 99%